2013
DOI: 10.3109/09513590.2013.777419
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Essure hysteroscopic sterilization – 5 years follow up of 1200 women

Abstract: Essure has the lowest Pearl index never published being the most effective permanent birth control system to date. Unintended pregnancies tend to occur in the first year after the insertion, and can be avoided encouraging women to accomplish the protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A second sterilization procedure following hysteroscopic sterilization is a well-identified risk already described in phase 2 and 3 studies, in which the risk varied between 4.0% and 4.5%. In the present study, this risk was 4.1% at the 1-year follow-up, comparable with that reported in previous studies conducted in real-life conditions in patients who received care in public or private hospitals and much higher than after laparoscopic sterilization.…”
Section: Discussionsupporting
confidence: 91%
“…A second sterilization procedure following hysteroscopic sterilization is a well-identified risk already described in phase 2 and 3 studies, in which the risk varied between 4.0% and 4.5%. In the present study, this risk was 4.1% at the 1-year follow-up, comparable with that reported in previous studies conducted in real-life conditions in patients who received care in public or private hospitals and much higher than after laparoscopic sterilization.…”
Section: Discussionsupporting
confidence: 91%
“…37 One 5-year follow-up study reported a failure rate of 0.25%. 38 Clinical experience with Essure has demonstrated significantly more loss to follow-up for the confirmatory HSG than expected. Compliance with the required follow-up HSG varies, from 13% to 94%.…”
Section: Placement Of Microinserts Via Hysteroscopymentioning
confidence: 80%
“…The long-term effectiveness of transcervical sterilization still needs to be fully assessed. Studies of women who have undergone successful bilateral coil placement and who demonstrate complete bilateral occlusion have demonstrated cumulative failure rates of only 0.25 % over 5 years [ 221 ]. However, a recent decision analysis found that of all women who initiate this sterilization method, only 85-86 % are effectively sterilized at 3 months [ 222 ].…”
Section: Sterilization Female Sterilization Methodsmentioning
confidence: 99%